Effect of pelvic compensation capacity on proximal junctional kyphosis: a stratified analysis of pelvic tilt in adult spinal deformity surgery - Xu, Yanjie; Fan, Changsheng; Li, Dongyue; Qiu, Yong; Liu, Zhen; Zhu, Zezhang (Journal of orthopaedic surgery and research, 2025)
Pelvic compensation, as quantified by the pelvic tilt (PT), has been identified as a crucial compensatory mechanism in patients with adult spinal deformity (ASD). However, it remains uncertain whether PT has important roles in predicting the occurrence of proximal junctional kyphosis (PJK). Therefore, the purpose of this study is to analyze the influence of pelvic compensation, specifically PT, on the development of PJK in ASD patients following the second sacral alar-iliac (S2AI) fixation. A total of 163 patients with ASD who underwent surgical treatment with S2AI fixation were retrospectively reviewed. According to the median value of pelvic tilt ratio (PTr) measured at baseline, patients were divided into the high PT group (PTr ≥ 0.6) and the low PT group (PTr < 0.6). Patients were further subdivided according to the degree of PT correction with the age-adjusted equation: PT = (age- 55) / 3 + 20. Patients who met the exact ± 10-year threshold for age-adjusted targets were assigned to group I (ideal correction). Patients whose correction deviated by more than 10 years above or below their age were classified into group U (undercorrection) and group O (overcorrection), respectively. Demographic, surgical, and radiographic parameters and the rates of PJK were compared between groups. Patients in the high PT group had significantly lower baseline TK, LL, as well as greater PI-LL and T1PA compared with the low PT group (all P < 0.05). Notably, the incidence of PJK was significantly higher in the high PT group compared to the low PT group (43.2% vs. 12.2%, χ²=19.612, P < 0.001). Further stratification by age-adjusted PT correction revealed significant differences in radiographic parameters across the subsets within both the low and high PT groups. In addition, among patients in the high PT group, the incidence of PJK was significantly lower in the overcorrected PT group (11/38, 28.9%) than under- (14/23, 60.9%) and ideal correction (10/20, 50%) of PT (χ²=6.449, P = 0.040). Patients in the high PT group, representing those with exhausted pelvic compensatory capacity, had a significantly higher risk of PJK compared to the low PT group. Further stratification by postoperative age-adjusted PT correction revealed that, within the high PT group, overcorrection of PT was associated with the lowest incidence of PJK, while undercorrection presented the highest risk. These findings suggest that patients with substantial baseline pelvic decompensation may benefit from a more aggressive PT correction to provide a stable foundation for spinal constructs and improve clinical outcomes in ASD surgery.